Exploring The Implementation of Artificial Intelligence in Islamic Education: A Systematic Literature Review - Amilusholihah, Amilusholihah; Ramadhan, Narendra Jumadil Haikal (Ngaji: Jurnal Pendidikan Islam, 2025)
The integration of Artificial Intelligence (AI) in Islamic education is changing the landscape of religious learning, in line with the broader trends of the 5.0 Industrial Revolution. The application of AI in Islamic education offers innovative ways to enhance the learning experience, expand access to religious knowledge, and provide a comprehensive educational pathway. However, it is clear that there is a lack of systematic literature that explicitly addresses the application of AI in Islamic education. This study aims to investigate the application of Artificial Intelligence (AI) in Islamic education, examining its potential to enhance personalized learning and educational accessibility. To answer the research questions, the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were used to systematically identify 18 of the 379 articles, covering the period 2022 to 2024, and retrieved from three databases, namely Scopus, Google Scholar, and ERIC, according to the established exclusion and inclusion criteria. The results show that (1) AI effectively improves students’ understanding, motivation, critical thinking skills, creativity, and efficiency in Islamic education. (2) Challenges include ethical issues, privacy concerns, and changing teacher roles. (3) Ethical considerations ensure that AI applications are aligned with Islamic principles and promote responsible use. It is recommended that stakeholders develop guidelines to balance technological advancement with the maintenance of ethical and spiritual principles.   ABSTRAK: Integrasi Kecerdasan Buatan (AI) dalam pendidikan Islam mengubah lanskap pembelajaran agama, sejalan dengan tren Revolusi Industri 5.0 yang lebih luas. Penerapan AI dalam pendidikan Islam menawarkan cara-cara inovatif untuk meningkatkan pengalaman belajar, memperluas akses ke pengetahuan agama, dan menyediakan jalur pendidikan yang komprehensif. Namun, jelas bahwa ada kurangnya literatur sistematis yang secara eksplisit membahas penerapan AI dalam pendidikan Islam. Penelitian ini bertujuan untuk menyelidiki penerapan Kecerdasan Buatan (AI) dalam pendidikan Islam, memeriksa potensinya untuk meningkatkan pembelajaran yang dipersonalisasi dan aksesibilitas pendidikan. Untuk menjawab pertanyaan penelitian, pedoman PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) digunakan untuk mengidentifikasi secara sistematis 18 dari 379 artikel, yang mencakup periode 2022 hingga 2024, dan diambil dari tiga basis data, yaitu Scopus, Google Scholar, dan ERIC, sesuai dengan kriteria eksklusi dan inklusi yang ditetapkan. Hasil penelitian menunjukkan bahwa (1) AI efektif meningkatkan pemahaman, motivasi, keterampilan berpikir kritis, kreativitas, dan efisiensi siswa dalam pendidikan Islam. (2) Tantangannya meliputi masalah etika, masalah privasi, dan perubahan peran guru. (3) Pertimbangan etika memastikan bahwa aplikasi AI selaras dengan prinsip-prinsip Islam dan mendorong penggunaan yang bertanggung jawab. Disarankan agar para pemangku kepentingan mengembangkan pedoman untuk menyeimbangkan kemajuan teknologi dengan pemeliharaan prinsip-prinsip etika dan spiritual. Kata kunci: Kecerdasan Buatan, Pendidikan Islam, Efektivitas AI, Tantangan AI, Pertimbangan Etika